Pengembangan Sistem Monitoring Heat Index dan UV Index Berbasis IoT Menggunakan ESP8266 di Kabupaten Sikka - Isma Alip; Zakaria Al Farizi; Nurfadilah (Piston: Jurnal Teknologi, 2026)
This study developed an Internet of Things (IoT)-based heat indeks and UV Index monitoring system using ESP8266 in Sikka Regency, East Nusa Tenggara, which has high levels of ultraviolet radiation and environmental temperature. The study aimed to monitor temperature, humidity, UV intensity, and heat index in real time through the ThingSpeak platform. The research method used the System Development Life Cycle (SDLC) approach, which includes planning, requirements analysis, design, implementation, testing, and system evaluation stages. Data collection was conducted at the Sikka Meteorological Agency from 07:00 to 19:00 WITA. The results showed that the system had good accuracy with a temperature regression value of R² = 0.9945 and humidity regression value of R² = 0.8286, as well as an average heat index difference of 0.4 °C compared to reference data. The developed system is considered feasible for environmental monitoring and mitigation of health risks caused by heat exposure and ultraviolet radiation. Future research can be improved by adding more accurate sensors and integrating automatic notification features based on applications.